The Prognostic Value of Early Warning Scores in Predicting Mortality among Stroke Patients: A Systematic Review - Hariyono, Rudi; Rofi'ah, Ika Ainur (Kirana Publisher (KNPub), 2025)
Stroke remains a leading global cause of mortality and disability, necessitating effective tools for early risk stratification. This systematic review evaluates the prognostic performance of Early Warning Scores (EWS)—MEWS, NEWS, and NEWS2—in predicting in-hospital mortality among stroke patients. Five studies published between 2021 and 2025 were included, encompassing diverse stroke subtypes and care settings. Across studies, higher EWS values were consistently associated with increased mortality risk, with odds ratios ranging from 2.44 to 3.21 and AUROC values between 0.69 and 0.79. NEWS2 generally outperformed MEWS and NEWS. Importantly, models incorporating neurological assessments, particularly the Glasgow Coma Scale (GCS), significantly improved predictive accuracy (AUROC 0.87). While EWS are valuable for early detection of deterioration, their performance in stroke is enhanced by integrating neurological parameters. These findings support the development of combined scoring systems and digital integration to optimize early intervention strategies in acute stroke care across varied healthcare settings.